Checklist of mangrove snails (Gastropoda: Mollusca) on the coast of Lamongan District, East Java, Indonesia - Wahyu Isroni; Putri D.W. Sari; Luthfiana A. Sari; Kiki Daniel; Josie South; ‪R. Adharyan Islamy‬; Pandu Y.A.P. Wirabuana; ‪Veryl Hasan‬ (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Isroni W, Sari PDW, Sari LA, Daniel K, South J, Islamy RA, Wirabuana PYAP, Hasan V. 2023. Checklist of mangrove snails (Gastropoda: Mollusca) on the coast of Lamongan District, East Java, Indonesia. Biodiversitas 24: 1676-1685. Mangroves are crucial transition zone ecosystems providing sheltered nursery zones and abundant marine and terrestrial biota resources. Mangrove snails (Gastropoda: Mollusca) are ecologically important ecosystem engineers, trophic links for higher predators, and a source of human food and livelihoods. Mangrove snails are also ideal bioindicators to monitor environmental pollution. A strong baseline understanding of current richness and distribution is therefore important. Thus, this study provides data on the species composition of mangrove snails on the north coast of Lamongan District, East Java, Indonesia. Sampling was conducted during low tide at four stations from September to November 2022 using square transects. Ten families consisted of Cerithiidae, Cypraeidae, Fasciolariidae, Muricidae, Naticadae, Neritidae, Plaxidae, Potamididae, Trochidae, and Turbinidae comprising 20 genera and 24 species. The most dominant family found is Muricidae, with six genera and eight species. Most mangrove snails were found in rocky, sandy substrates, around trees, and mangrove roots. Gastropods observed in this study were alive and dead (i.e., empty shells). We suspect that there is still much-hidden diversity of Gastropoda in this region. Therefore, we suggest that future work addresses differences in microhabitat and snail morphology with quantitative and semi-quantitative methods to understand distribution drivers and ecological roles better.